Utilization and Satisfaction of Beneficiaries Regarding Take Home Ration Provided At Urban Anganwadis of Ahmedabad, Gujarat - Ashadevi Sisodiya; Fatema Kachhawala; Aparajita Shukla (Healthline, 2022)
Introduction: Nutrition is fundamental to human health and development. The Take Home Ration (THR) program provides fortified rations for 6 months to 3 years normal children and severely underweight children up to 6 years, adolescent girls, pregnant women, lactating women through Anganwadis (AW). The National Nutrition Missions have targeted to decrease under nutrition by 3% each year. Present study was conducted with an objective was to assess the utilization and satisfaction level of beneficiaries regarding THR and to identify challenges faced by AWW related to THR. Method: A cross-sectional study was conducted at 40 Aanganwadis situated in the urban field practice area of the institute. Interview of all the (40) Anganwadi workers were conducted regarding implementation of THR Program. For assessing the utilization and satisfaction regarding THR, total 200 beneficiaries were selected from five different groups viz; 6 months to 3-year children, severely underweight children up to 6 years, Adolescent girls, Pregnant women and lactating women. Purposive sampling was used for selection of beneficiaries considering availability of beneficiaries at the time of study. Frequency and percentages were calculated for quantitative data. Results: Knowledge of AWW regarding THR scheme was good. Out of 200 beneficiaries, 97.5% beneficiaries were obtaining THR packets from anganwadis, out of which 66% beneficiaries were using them regularly. Around 36% of beneficiaries weren’t satisfied with THR provided to them. Major challenges faced by beneficiaries were: Lack of variety, not possible to make separate food items from THR due to time constraints and lack of knowledge.Conclusion: Utilization of THR among beneficiaries was not satisfactory. Most of the beneficiaries were disappointed with taste of the THR. Beneficiaries strongly recommended for improvement in taste and flavour. Awareness regarding THR scheme was satisfactory among AWW. Biggest challenge faced by AWW was to convince beneficiaries regarding intended benefits of THR and regular usage of the same